Malignancy course of pituitary adenoma in MEN1 syndrome: Clinical-Neuroradiological signs - Francesca Incandela; Paola Feraco; Valeria Putortì; Laura Geraci; Giuseppe Salvaggio; Caterina Sarno; Giuseppe La Tona; Giovanni Lasio; Cesare Gagliardo (European Journal of Radiology Open, 2020)
Pituitary carcinomas (PCa) are extremely rare, indistinguishable from pituitary adenomas on histopathological grounds and have a poor prognosis. Most PCa start as PRL or ACTH secreting tumors in males, with relapsing invasive behaviour, refractoriness to medical and radiotherapy and increasing hormonal levels. The presence of distant metastases is still required for the diagnosis of PCa. The association with genetic endocrine diseases must be taken into account, since it adds further risk of evolution towards malignancy. Intradural spinal metastases have also been reported, so a complete craniospinal MR evaluation is recommended, when clinically indicated. We report a case of PCa, associated with MEN1 syndrome, with evidence of meningeal spread to the tentorium cerebelli, clival dura and spinal drop metastases mimicking spinal nerves schwannomas.